The Vietnamese calligraphy: the past and present - Donchenko A.I. (Восточная Азия: факты и аналитика, 2019)
This article is devoted to the emergence and development of the art of calligraphy in Vietnam and how the long history of the cultural influence of China has affected the appearance of a new and distinctive trend in the world art - the contemporary Vietnamese calligraphy. A comparative analysis of some norms of Chinese calligraphy and contemporary Vietnamese calligraphy is also carried out. The history of Vietnamese writing has come a long and difficult way, having passed, after a long period of using the Chinese character, to the creation of their own writing based on the Latin alphabet. Currently, the art of beautiful writing in Vietnam is undergoing major changes, but it can already be stated with confidence that the appearance of the modern Vietnamese calligraphy has become a new stage in the development of the national art of this country. Combining the culture of West and East, modern Vietnamese calligraphy has become a harmonious continuation of cultural traditions.